2019
DOI: 10.32479/ijefi.8157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quality of Good Corporate Governance Disclosure, Leverage and Firm Size on Profitability of Isalmic Commercial Banks

Abstract: The purpose of this study was to determine the effect of the quality of disclosure of good corporate governance (GCG), leverage, and firm size on profitability in Islamic commercial banks in Indonesia and Malaysia. The data used in this study were obtained from the website of each bank in the period 2011-2017 with a total sample of 16 Islamic commercial banks. The data analysis technique used in this study is panel data regression analysis. The results showed that the quality of GCG disclosure and leverage had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
2
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(94 citation statements)
references
References 5 publications
(7 reference statements)
3
43
2
19
Order By: Relevance
“…The effect of the corporate governance on the IBs financial performance shows mixed results. For example, Harisa et al (2019) reported the impact of the corporate governance on the IBs profitability in Indonesia and Malaysia from 2011 to 2017. Using the panel data regression analysis, they showed that the governance does not affect the profitability measured by ROA.…”
Section: Shariah Governance and Financial Performancementioning
confidence: 99%
“…The effect of the corporate governance on the IBs financial performance shows mixed results. For example, Harisa et al (2019) reported the impact of the corporate governance on the IBs profitability in Indonesia and Malaysia from 2011 to 2017. Using the panel data regression analysis, they showed that the governance does not affect the profitability measured by ROA.…”
Section: Shariah Governance and Financial Performancementioning
confidence: 99%
“…Profitability is measured using Return on Assets (ROA) is often a major concern because its ability to project the company's past earnings to be used as an evaluation in the future [31]. Banks' ability to create income from total assets is launched with Return on Assets (ROA) [32]. If this is more significant, a company's possibility in a problematic condition is less because the resulting profit increases.…”
Section: Profitabilitymentioning
confidence: 99%
“…with profitability (Chen, Firth, and Rui, 2006). Meanwhile, there is no relationship between debt and profitability (Amanda, 2019;Harisa et al, 2019;Kebewar and Shah, 2012).…”
Section: Debt Financing and Profitabilitymentioning
confidence: 99%
“…Conversely, there is a positive association between debt and profitability (Harelimana, 2017;Holz, 2002;Kartikasari and Merianti, 2016). Meanwhile, debt is not associated with profitability (Amanda, 2019;Hadiah, 2016;Harisa, Adam, and Meutia, 2019;Kebewar and Shah, 2012).…”
Section: Introductionmentioning
confidence: 96%